2021
DOI: 10.3390/geosciences11090374
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Volcanic Thermohaline Fluctuations of Tagoro Submarine Volcano (El Hierro Island, Canary Islands, Spain)

Abstract: Temperature and conductivity fluctuations caused by the hydrothermal emissions released during the degasification stage of the Tagoro submarine volcano (Canary Islands, Spain) have been analysed as a robust proxy for characterising and forecasting the activity of the system. A total of 21 conductivity-temperature-depth time series were gathered on a regular high-resolution grid over the main crater of Tagoro volcano. Temperature and conductivity time series, as manifestations of stochastic events, were investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…The CTD data have been sorted and analyzed using the Generalized Moments Method (GMM), a relatively recently developed mathematical method with various applications in finance time series [28][29][30] and environmental cases [29,31,32]. Our group has successfully used the same modeling method previously to identify the underlying stochastic processes driving the activity of other volcanoes, such as the Kolumbo volcano [33] and Nisyros volcano [34,35], followed by others, e.g., in the case of the shallow underwater volcano El Hierro [36,37]. Previous studies yielded exciting aspects of the underlying dynamics of hydrothermal vent fields during rest and unrest periods.…”
Section: Introductionmentioning
confidence: 99%
“…The CTD data have been sorted and analyzed using the Generalized Moments Method (GMM), a relatively recently developed mathematical method with various applications in finance time series [28][29][30] and environmental cases [29,31,32]. Our group has successfully used the same modeling method previously to identify the underlying stochastic processes driving the activity of other volcanoes, such as the Kolumbo volcano [33] and Nisyros volcano [34,35], followed by others, e.g., in the case of the shallow underwater volcano El Hierro [36,37]. Previous studies yielded exciting aspects of the underlying dynamics of hydrothermal vent fields during rest and unrest periods.…”
Section: Introductionmentioning
confidence: 99%
“…Two studies, Olivè Abellò et al [2] and Dura et al [3], applied stochastic calculus tools on temporal series of seawater conductivity and temperature measurements carried out in the water column characterized by the presence of vent of fluids from the seafloor. Fluctuations of the conductivity and temperature properties provide meaningful information about the state of activity of the hydrothermal systems.…”
mentioning
confidence: 99%
“…The described statistical technique could be usefully tested in other volcanic contexts in order to determine a large case history of time series of conductivity and temperature fluctuation in different volcanic contexts and phase of activity. In particular, Abello et al [2] showed the results of sampling points located on the main crater of the Tangoro submarine volcano. This latter, placed close to the El Hierro island in the Canarian Archipelago (Spain), was subjected to recent volcanic activity, and its post-eruptive activity is actually strictly monitored.…”
mentioning
confidence: 99%